Hierarchical Structure Fabrication of IPMC Strain Sensor With High Sensitivity - Chang, Longfei; Wang, Dongping; Hu, Jiajia; Li, Yan; Wang, Yanjie; Hu, Ying (Frontiers in Materials, 2021)
In this paper, a biological template method is introduced and investigated to fabricate Ionic polymer-metal composite (IPMC) strain sensor with bionic hierarchical structures. We utilized the multi-level structure of reed leaf surface, which can improve the contact area between the substrate and the electrode layers. Hierarchical structures were observed on the IPMC samples, including pyramid strips with the width in the range of 60μm to 80μm as well as synaptic scatters with diameter around 10μm. In addition, five kinds of sensors with different interface structures were obtained by combining the traditional microneedle roller roughening and chemical plating processes. It was found that the IPMC sensor with reed-leaf and microneedle structure on each side presented the best performance, along with a high linearity, a sensitivity of 62.5 mV/1% and a large generated voltage peak under given mechanical stimuli, which is 3.7 times that of the sample fabricated without roughening.